The desulfurization of heavy oils and residua - Speight, James G. (Chemical industries, 2000)
This volume expands and updates information on the technological aspects of refining heavy oils, residua, bitumen, and other high-sulphur feedstocks. It focuses on the range of nest-generation refining processes.